PENGUATAN DINAMIKA KELOMPOK DALAM MENINGKATKAN KAPASITAS KELEMBAGAAN USAHA SAPI POTONG - Sri Yenny Pateda; Fauzan Zakaria (xxxx-xxxx, 2022)
This study aims to determine the effect of group dynamics on the institutional capacity of beef cattle farmer groups in Gorontalo Regency. This research was conducted in Gorontalo Regency in February–June 2018. The method used in this study is a quantitative method. Determination of the sample is done by multistage sampling. The number of samples is 120 members of farmer groups. Data processing using Structural Equation Modeling (SEM) analysis on the AMOS program. The results showed that group dynamics affected the institutional capacity of farmers by 0.859. Each dynamics indicator contributes a good average including clear group goals 61.4% group structure 65.6%, task function 67.6%, group development coaching 58%, cohesiveness 60.2%, atmosphere 50% , 54.3% effectiveness, 63% pressure group and 74% desire group. The institutional capacity development of farmer groups cannot be separated from group dynamics that have a positive effect. Farmer groups as a forum that has the potential to move its members to interact and work together. The level of group dynamics is quite good, but the role of breeders must be more optimal in participating in the activities of the beef cattle business group Keywords: Cattle, Group dynamics, Institutional capacity